2020
DOI: 10.3390/molecules25112485
|View full text |Cite
|
Sign up to set email alerts
|

Natural Nitrogenous Sesquiterpenoids and Their Bioactivity: A Review

Abstract: Nitrogenous sesquiterpenoids fromnatural sourcesare rare, so unsurprisingly neither the potentially valuable bioactivity nor thebroad structural diversity of nitrogenous sesquiterpenoids has been reviewed before. This report covers the progressduring the decade from 2010 to February 2020 on the isolation, identification, and bioactivity of 391 nitrogen-containing natural sesquiterpenes from terrestrial plant, marine organisms, and microorganisms. This complete and in-depth reviewshouldbe helpful for discoverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…According to previous studies, flavonoids are important in promoting plant growth, especially root growth ( Khalid et al, 2019 ), and indoles are essential in the synthesis of plant growth hormones ( Baumann et al, 2017 ). In addition, sesquiterpenoids are effective in promoting plant growth and resistance to various adversities ( Chen et al, 2020a ). Accordingly, the shift of metabolic pathways mentioned above may contribute to promoted growth of cucumber in artificial cultivation substrates than in soils, which was observed during the experiment (data not provided).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, flavonoids are important in promoting plant growth, especially root growth ( Khalid et al, 2019 ), and indoles are essential in the synthesis of plant growth hormones ( Baumann et al, 2017 ). In addition, sesquiterpenoids are effective in promoting plant growth and resistance to various adversities ( Chen et al, 2020a ). Accordingly, the shift of metabolic pathways mentioned above may contribute to promoted growth of cucumber in artificial cultivation substrates than in soils, which was observed during the experiment (data not provided).…”
Section: Discussionmentioning
confidence: 99%
“…Sesquiterpenoids are the most abundant members of natural terpenoids because of their various structures and notable bioactivities. The chemical components of sesquiterpenoids had been found in plants, animals, microorganisms and marine organisms [ 117 , 118 ]. A series of sesquiterpenoids ( 175 – 184 and 195 ) were isolated from a strain of Phomopsis sp.…”
Section: Bioactive Secondary Metabolites From Phomopsis mentioning
confidence: 99%
“…Numerous studies have been performed on the isolation and chemical and biological characterization, and these studies are still increasing. These investigations have also confirmed that families such as alkaloids [ 1 ], peptides [ 2 ], phenoxazines [ 3 ], amines [ 4 ], or nitrogenous sesquiterpenoids [ 5 ] could show outstanding activities of pharmacological or agronomic interest. The alkaloid family is one of the most relevant of these, given its production by a wide range of living beings, its structural variety, as well as the biological activities that have been discovered a long time ago.…”
Section: Introductionmentioning
confidence: 81%